DESIGN AND IMPLEMENTATION OF AN AUTOMATED COMPUTER SYSTEM FOR THE ONLINE SOLICITING AND MANAGEMENT OF OPERATIONAL PERMIT ISSUANCE. "Case of the Provincial Environmental Coordination" - ESABE MANDEBO Rodriguez; Makimi Ngeme Patrick (IJRDO -Journal of Computer Science Engineering, 2025)
Currently, many analysts, researchers and scientists are concerned about the automation of companies so that managers can ensure good administration, through information technology through management information technology. The latter could not only manage information, but above all resolve the difficulties specific to human activity while maximizing revenue.